ANALISIS TINGKAT KEPUASAN WISATAWAN BERDASARKAN ATRAKSI, AMENITAS DAN AKSESIBILITAS DI TELAGA MENJER, WONOSOBO. - Lenny Kurnia Octaviani; Vincentia Defista Febe Aurora (UHN IGB Sugriwa Denpasar, 2024)
The increase and decrease in the number of tourist visits is caused by varying levels of satisfaction. Factors that affect tourist satisfaction are attractions, amenities, and accessibility. This study aims to determine the overall level of tourist satisfaction based on attractions, amenity, and accessibility at Telaga Menjer, to determine the level of conformity of expectations and reality in tourists, and to determine the attributes expected by Telaga Menjer tourists. Survey, quantitative is the research method used in this study. Sources of data collection in this study used primary sources in the form of questionnaires and secondary sources such as journals, books, and related articles. In this study, data analysis was carried out using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of this study indicate that the overall level of tourist satisfaction based on attractions, amenities, and accessibility is included in the satisfied category with the results of the CSI value of 77.25%. The results of Importance Performance Analysis (IPA) show that the average value of the level of conformity (Tki) is 87.22%, which means that the level of conformity is good because it is close to 100%. The results of the IPA are also used to map the Cartesian diagram. The Cartesian diagram shows that the attributes that are highly expected by tourists but have unsatisfactory reality / performance are in quadrant A, namely road signs / instructions, safety signs, road conditions, and transportation access. Referring to the research findings, the advice that can be given is that Telaga Menjer should prioritize improvements to attributes that have high expectation values but low reality or performance values